2000
DOI: 10.1590/s1516-35982000000600024
|View full text |Cite
|
Sign up to set email alerts
|

Influência de fatores antinutricionais da leucena (Leucaena leucocephala e Leucaena cunningan) e do feijão guandu (Cajanus cajan) sobre o epitélio intestinal e o desempenho de frangos de corte

Abstract: RESUMO -Um experimento foi conduzido para avaliar a influência de fatores antinutricionais de alguns alimentos sobre o epitélio intestinal e o desempenho de frangos de corte. Foram utilizados 480 pintos de um dia de idade, em um delineamento inteiramente casualizado com quatro tratamentos (A = ração testemunha à base de milho e soja; B = ração contendo Leucaena leucocephala -6% [LL]; C = ração contendo Leucaena cunningan -6% [LC] e D = ração contendo feijão guandu -Cajanus cajan -20% [CC]), quatro repetições e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 9 publications
1
5
1
12
Order By: Relevance
“…Consistent with the results of the present study, Uni et al (1998), Oliveira et al (2000), and Geyra et al (2001) reported that the duodenum and the jejunum present high cell proliferation and migration rates, as well as high villi and deep crypts, because they are submitted to stronger aggression and stimuli. Ribeiro et al (2002) did not find any effects of increasing corn particle size on duodenal morphology (villus number and height) in 21-to 42-d-old male broilers, but that villus number and height increased with age.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with the results of the present study, Uni et al (1998), Oliveira et al (2000), and Geyra et al (2001) reported that the duodenum and the jejunum present high cell proliferation and migration rates, as well as high villi and deep crypts, because they are submitted to stronger aggression and stimuli. Ribeiro et al (2002) did not find any effects of increasing corn particle size on duodenal morphology (villus number and height) in 21-to 42-d-old male broilers, but that villus number and height increased with age.…”
Section: Resultssupporting
confidence: 92%
“…However, the above differed from reports by Oliveira et al (2000) that 6% of leucaena hay impaired the performance of broilers. It should be underscored that variations may occur in the chemical composition and in the amount of nutritional factors in leucaena due to type of cultivar, soil, climate of the cultivated area (D'MELLO; ACAMOVIC, 1989).…”
Section: Resultscontrasting
confidence: 98%
“…Bhatnagar et al (1996) tested LLH inclusion levels 5, 10 and 20% in the diets of commercial laying hens and registered that a significant decrease in egg production, weight and mass of eggs and high diet intake occurred only at 20% inclusion level. On the other hand, Oliveira et al (2000) evaluated two species of leucaena (L. leucocephala and L. cunningham) at level up to 6% inclusion in the diet and reported a significant decrease in weight gain in 1 to 21-day-old fowls.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main features that make the broiler chicken so productive is the great capacity of its intestinal epithelium to absorb nutrients (Oliveira et al, 2000). According to Cera et al (1988), the absorption capacity of the small intestine is proportional to the number and size of the intestinal villi and the surface area available for absorption.…”
Section: Effects Of Heat Stress On Cell Dynamics Of Broiler Chicken Smentioning
confidence: 99%